N, N-Dimethyltryptamine (DMT), an Endogenous Hallucinogen: Past, Present, and Future Research to Determine Its Role and Function - Barker, Steven A. (Frontiers in Neuroscience, 2018)
Abstract This report provides a historical overview of research concerning the endogenous hallucinogen N, N-dimethyltryptamine (DMT), focusing on data regarding its biosynthesis and metabolism in the brain and peripheral tissues, methods and results for DMT detection in body fluids and brain, new sites of action for DMT, and new data regarding its possible physiological and therapeutic roles. Research that further elaborates its consideration as a putative neurotransmitter is also addressed. Taking these studies together, the report proposes several new directions and experiments to ascertain the role of DMT in the brain, including brain mapping of enzymes responsible for the biosynthesis of DMT, further studies to elaborate its presence and role in the pineal gland, a reconsideration of binding site data, and new administration and imaging studies. The need to resolve the “natural” role of an endogenous hallucinogen from the effects observed from peripheral administration are also emphasized.